Pervasive Introgression During Rapid Diversification of the European Mountain Genus Soldanella (L.) (Primulaceae) - Slovák, Marek; Melichárková, Andrea; Štubňová, Eliška Gbúrová; Kučera, Jaromír; Mandáková, Terezie; Smyčka, Jan; Lavergne, Sébastien; Passalacqua, Nicodemo Giuseppe; Vďačný, Peter; Paun, Ovidiu (Systematic biology, 2023)
Hybridization is a key mechanism involved in lineage diversification and speciation, especially in ecosystems that experienced repeated environmental oscillations. Recently radiated plant groups, which have evolved in mountain ecosystems impacted by historical climate change provide an excellent model system for studying the impact of gene flow on speciation. We combined organellar (whole-plastome) and nuclear genomic data (RAD-seq) with a cytogenetic approach (rDNA FISH) to investigate the effects of hybridization and introgression on evolution and speciation in the genus Soldanella (snowbells, Primulaceae). Pervasive introgression has already occurred among ancestral lineages of snowbells and has persisted throughout the entire evolutionary history of the genus, regardless of the ecology, cytotype, or distribution range size of the affected species. The highest extent of introgression has been detected in the Carpathian species, which is also reflected in their extensive karyotype variation. Introgression occurred even between species with dysploid and euploid cytotypes, which were considered to be reproductively isolated. The magnitude of introgression detected in snowbells is unprecedented in other mountain genera of the European Alpine System investigated hitherto. Our study stresses the prominent evolutionary role of hybridization in facilitating speciation and diversification on the one hand, but also enriching previously isolated genetic pools. [chloroplast capture; diversification; dysploidy; European Alpine system; introgression; nuclear-cytoplasmic discordance; ribosomal DNA.].
Keywords: genom; Primulaceae; Ecology; ekosystém; DNA, Ribosomal; Phylogeny; fylogeneze; Ecosystem; ribozomální DNA; ekologie; Genome